1999
DOI: 10.1177/002194369903600301
|View full text |Cite
|
Sign up to set email alerts
|

Negative Messages as Strategic Communication: A Case Study of a New Zealand Company's Annual Executive Letter

Abstract: We argue here that being negative can, in certain contexts, make strategic sense. Making extensive reference to context, we analyze a single annual executive letter written by the director of a small New Zealand business. The letter appears to focus on problems. These problems are, however, relatively minor ones that had either already been solved or were in the process of resolution when the letter was written. These problems appear to serve three functions: to distract attention from more serious issues, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Companies tend to apply different strategies to reveal bad news or losses: they focus on future achievements, apply passive construction, process verbs and non-human agents or inanimate nominal group, they use multiple narrators and tend to be less informative (Kohut & Segars, 1992;Thomas, 1997;Jamson, 2000;Roger, 2000). Another important finding was that bad news could be used strategically to convey the message that the managers are experts and can handle difficult situations (Crombie & Samujh, 1999). The studies that analyzed the text for metadiscourse items discovered that the communicative purpose of the text influences the choice of metadiscourse items and there exist cross cultural variations with regard to their use (Hyland, 1998;De Groot, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Companies tend to apply different strategies to reveal bad news or losses: they focus on future achievements, apply passive construction, process verbs and non-human agents or inanimate nominal group, they use multiple narrators and tend to be less informative (Kohut & Segars, 1992;Thomas, 1997;Jamson, 2000;Roger, 2000). Another important finding was that bad news could be used strategically to convey the message that the managers are experts and can handle difficult situations (Crombie & Samujh, 1999). The studies that analyzed the text for metadiscourse items discovered that the communicative purpose of the text influences the choice of metadiscourse items and there exist cross cultural variations with regard to their use (Hyland, 1998;De Groot, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…3.1.1.4 Negative theme as a communication strategy Crombie and Samujh (1999) claimed that negative messages or themes could sometimes be used as a communication strategy. They conducted a case study on the content of one annual executive letter of a small New Zealand company and considered the surface linguistic features, immediately recoverable meanings and meanings that can only be recovered through considering the context.…”
Section: Use Of Metadiscoursal Resources In Carsmentioning
confidence: 99%
“…The first are studies conducted on content analysis and theme of good news and bad news (Clatworthy & Jones, 2006;Conaway & Wardrope, 2010;Crombie & Samujh, 1999;De Groot, Korzilius, Nickerson & Gerritsen, 2006;Jamson, 2000;Kohut & Segars, 1992;Rogers, 2000;Thomas, 1997;Smith & Taffler, 2000). These studies found that companies resort to different strategies to reveal bad news or losses e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, they usually function as the introductory section of CARs. In addition, according to Plung and Montgomery (2004), a survey was conducted by Security and Exchange Commission (SEC) which revealed that management foreword is the most widely read section of CARs and most of the readers go through this section first in search of information as it contains a report of the company's past financial and non-financial accomplishments plus future plans (Conaway & Wardrope, 2010;Crombie & Samujh, 1999;De Groot, Korzilius, Ickerson & Gerritsen, 2006;De Groot, 2008;Hyland, 1998;Jamson, 2000;Kohut & Segars, 1992;Thomas, 1997). Most importantly, the credibility of annual reports depends on a truthful management foreword which tells the story as it is, accepts the responsibilities for losses instead of denying it or attributing it to outside factors, and reports major changes in the company which influences the profit making of the company.…”
Section: Introductionmentioning
confidence: 99%
“…While Limaye's articles offer theoretical perspectives on explanation in negative correspondences, his study does not examine correspondences created within -real‖ rhetorical contexts. In fact, few recent studies examine messages produced within the context of an actual organization, except for Crombie and Samujh (1999) and Schryer (2000). Schyer (2000) attempts to determine the -effectiveness‖ of insurance claim letters denying long-term disability benefits and understand the letters' production process.…”
Section: Recall Noticesmentioning
confidence: 99%